Exploration of the Views of Eshop Managers on eWOM in the Czech Republic - Laboutka, Filip (2020)
This study focuses on views of e-shop managers on eWOM in Czech Republic. It aims to explore and investigate managers’ knowledge, behaviour, and opinions on online communication regarding their business and products. The research method that is used is explorative qualitative research using semi-structured interviews to collect data. Among findings of the research is that participating e-shop managers have a gist of eWOM, monitor independent platforms, know that responding to negative eWOM is beneficial to their brand, know which eWOM channel is the most important for their business, and respond to negative eWOM with caution. Apart of these findings, there are several observations related to negative reviews and established theory. These observations as well as findings of this research pave the way for more extensive qualitative research of this issue.